1990
DOI: 10.1001/archderm.1990.01670320067010
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens in Lichen Sclerosus et Atrophicus

Abstract: Several reports have found conflicting data regarding the association between lichen sclerosus et atrophicus (LSA) and HLA types. Association with HLA-A31 and -B40 has been noted, whereas another report found no correlation. We are the first to specifically examine HLA types in white patients in the United States. We have found a significant association between LSA and HLA-A29 and -B44 individually and an even stronger association with the combination of A29 and B44. A review of previous LSA-HLA studies, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…The pathogeny of LSA is completely unknown. Genetic, hormonal and autoimmune factors [2, 3, 10, 11, 12, 13, 14]have been advocated. Pathological examination at early lesions of LSA shows hyperkeratosis, follicular plugging of the epidermis and vacuolar alteration of the basal layer.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogeny of LSA is completely unknown. Genetic, hormonal and autoimmune factors [2, 3, 10, 11, 12, 13, 14]have been advocated. Pathological examination at early lesions of LSA shows hyperkeratosis, follicular plugging of the epidermis and vacuolar alteration of the basal layer.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of BXO remains obscure. Genetic factors have been implicated in association with HLA subtypes [2], which may explain our observation of brothers, or of fathers and sons, presenting with this condition. Several publications [3,4] including ours, noted an increased incidence of other auto‐immune type conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of LS/BXO has yet to be determined and multiple theories have been proposed . Previous studies have identified an association between LS/BXO and systematic factors (autoimmune, genetic and/or hormonal) , as well as local causes (trauma, infection or radiation) . LS/BXO involvement of extragenital skin grafts used for genital reconstruction supports the theory that, when systematically predisposed skin is exposed to local factors of the genital region, the development of LS/BXO is induced .…”
Section: Discussionmentioning
confidence: 81%